2017
DOI: 10.5897/ajps2016.1450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wheat cultivars for slow rusting resistance to leaf rust (Puccinia trticina Eriks) in Ethiopia

Abstract: Leaf rust (Puccinia triticinaEriks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…This indicating that cultivars that were severely infected showed higher AUDPC values [58]. This positive correlation was in agreement with the results of other researchers on cereal-rust pathosystems [35,48,50,65]. Averagely the lowest r-value was obtained between infection rate and other parameters Table 4.…”
Section: Correlation Between Slow Rusting Parameters Of Wheat Stem Rustsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicating that cultivars that were severely infected showed higher AUDPC values [58]. This positive correlation was in agreement with the results of other researchers on cereal-rust pathosystems [35,48,50,65]. Averagely the lowest r-value was obtained between infection rate and other parameters Table 4.…”
Section: Correlation Between Slow Rusting Parameters Of Wheat Stem Rustsupporting
confidence: 90%
“…In spite of its importance to quantify the rate of disease development on the cultivars tested using infection rate to estimate partial resistance seemed unreliable when compared with FRS, CI and AUDPC because it could not identify different levels of partial resistance among the tested cultivar. Similarly, Hei [50] and Ali, et al [64] reported infection rate doesn"t yield consistent estimation for their study.…”
Section: Apparent Infection Ratementioning
confidence: 82%